STRENGTHENING MUHAMMADIYAH IDEOLOGY THROUGH WEBINER 'AISYIYAH, NORTH SUMATRA, FACES COVID 19 NEW NORMAL - Nadlrah Naimi; Nur Rahmah Amini (Proceeding International Seminar of Islamic Studies, 2021)
The explanation above has become our whole lesson that 'Aisyiyah cadres have an important role in dealing with the new normal covid 19. Right now we must have the almaun movement which is a potential strength in social activities, so that the enthusiasm of' Aisyiyah cadres and sympathizers continues to make changes good in strengthening Muhammadiyah ideology, especially in North Sumatra. Muhammadiyah is faced with a variety of ideological and political forces that are not always in line both in the Islamic context and Muhammadiyah's own mission, so that to a certain extent it demands ideological strength and fostering without having to be trapped in a monolithic ideological-political system of understanding completely absolute. There is a tendency among Muhammadiyah members and organizations to suggest a weakening or diminishing of the spirit of al-Islam and Muhammadiyah and commitment to the movement, so that the movement of the organization has decreased its militancy and spirit of jihad in facing various hardening problems and challenges. Ideological fostering in the context of cultivating Islamic and Muhammadiyah value systems is important both in efforts to consolidate and strengthen the movement as well as in the interest of maintaining continuity.Keywords: Muhammadiyah ideology, Aisyiyah, New Normal